Effects of Implementing a Brief Family Nursing Intervention With Hospitalized Oncology Patients and Their Families in Germany: A Quasi-Experimental Study. (November 2020) - Zimansky, Manuel; Stasielowicz, Lukasz; Franke, Inga; Remmers, Hartmut; Friedel, Heiko; Atzpodien, Jens
Family nursing, based on the Calgary Family and Intervention Models, was implemented in a German oncological inpatient unit to promote effective family functioning in the context of cancer care. The objective of this study was to investigate the effects of implementing family nursing care on several psychological and physical outcomes of patients and their family members. A quasi-experimental study with 214 patients with a cancer diagnosis and 122 family members was conducted. Findings indicate that the superiority of family nursing, when compared to traditional care, could not be confirmed with respect to patients' outcomes (psychological burden, social support, satisfaction with care) and family members' outcomes (psychological burden, physical complaints, satisfaction with care). Various factors, such as country-specific structures and challenges in implementing family nursing care on an inpatient unit, may have contributed to these findings. Further replication attempts in similar settings in other countries are needed to shed light on the factors impairing or promoting the implementation of family nursing in practice settings.